POLA KOMUNIKASI RUMAH SINGGAH MITRA AL-AKHYAR DALAM PROSES PEMBINAAN KEAGAMAAN ANAK JALANAN DI BANDAR LAMPUNG - hud leo perkasa maki; Ade Nur Istiani; Is Susanto (Ath Thariq Jurnal Dakwah dan Komunikasi, 2020)
The Street Kids, behind the negative sides of their social life environment, some of them still have nature to recognize their God. The existence of the street kids in Bandar Lampung keeps increasing everyday. In the other side, the government gives less attention to this case,so that the street kids become the citizen who are avoided by the society. The Homeless Shelter of Al-Akhyar is the non-governmental organization standing independently having awareness towards the existence of the street kids in Bandar Lampung. The organization which initiatively implementing religion development of the street kids. The Communication Pattern of the Homeless Shelter of Mitra Al-Akhyar in implementing the religion development ofthe street kids in Bandar Lampung based on the term of faith (Islamic Aqeedah), Islamic Syariah, and Moral. The communication patterns implemented in this case are conversation, story telling, parable, advice, attention, exemplary, habituation, and lecture.